Investigating the structure of Schwartz’s values scale: Evidence from the 2010 European Social Survey for Greece - Charalampi, Anastasia (The Greek Review of Social Research, 2023)
In order to approach the measurement of an attitude scale, the crucial question of its reliability and validity arises. The present study aims at investigating the theoretical structure and assessing the psychometric properties of the ten-dimensional Schwartz’s human values scale short form (PVQ-21). The investigation was based on the European Social Survey (ESS) Greek data of Round 5 (2010). The analysis produced two reliable and valid subscales: Openness to change and Self-transcendence. The results did not confirm the dimensionality of the Schwartz Human Values Scale as proposed in the literature. However, a useful methodological tool is provided to social scientists.